Reinforcing the Legal Basis of Undercover Buy as an Investigative Method in Criminal Procedure - Maharani, Asari Suci; Supardi, Supardi (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
In an effort to combat illegal drug trafficking, Law Number 35 of 2009 concerning Narcotics authorizes the National Narcotics Agency (BNN) to conduct special investigation techniques, one of which is the undercover buy technique. The research problem studied is how to regulate undercover buy techniques in the legal system in Indonesia and how to formulate the regulation of undercover buy provisions in an ideal criminal procedure law that does not conflict with legal principles. This study is a normative legal study that uses a regulatory approach and a contextual approach. The data sources are from regulations and legal literature. The results of the study indicate that the regulation of undercover buy techniques is normatively contained in the Narcotics Law and the implementation instructions that have been updated through the Decree of the Head of BNN Number SKEP/1205/IX/2000. However, these regulations are still minimal and not comprehensive, thus creating legal limitations that have the potential to cause investigators to apply for permits, especially in obtaining valid evidence according to criminal procedure law